On the effects of powder morphology on the post-comminution ballistic strength of ceramics. (February 2017) - Appleby-Thomas, G.J.; Wood, D.C.; Hameed, A.; Painter, J.; Fitzmaurice, B.
Highlights: A series of depth-of-penetration experiments have been conducted using comminuted ceramic analogues comprising cold-pressed ceramic compacts. Initial compact morphology was found to have a measurable influence on ballistic response. Under similar pressing pressures (e.g. with similar underlying microstructures), compact thicknesses were shown to have a marked effect on ballistic response. Findings from ballistic experiments were backed by a discrete series of shock experiments. Abstract: In this paper in order to try and elucidate the effects of particle morphology on ballistic response of comminuted systems, a series of experiments were carried out via the use of powder compacts with differing initial particle morphologies. This approach provided a route to readily manufacture comminuted armour analogues with significantly different microstructural compositions. In this study pre-formed 'fragmented-ceramic' analogues were cold-pressed using plasma-spray alumina powders with two differing initial morphologies (angular and spherical). These compacts were then impacted using 7.62 mm FFV AP (Förenade Fabriksverken Armour Piercing) rounds with the subsequent depth-of-penetration of the impacting projectile into backing Al 6082 blocks used to provide a measure of pressed ceramic ballistic response. When material areal density was accounted for via differing ballistic efficiency calculations a strong indication of particle morphology influence on post-impact ceramic properties was apparent. These results were reinforced by a separate small series of plate-impact experiments, whose results indicated that powder morphology had a strong influence on the nature of compact collapse.